Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19159342
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Life Events Outside the Workplace and Burnout: A Cross-Sectional Study on Nursing Assistants

Abstract: Background: Burnout, by definition, is related to adverse chronic workplace stressors. Life events outside the workplace have been associated with an increased risk of psychiatric morbidity. However, it is unknown whether life events outside the workplace increase the severity of burnout. Purpose: The aim of the study was to investigate the association between burnout and life events outside the workplace in nursing assistants. Methods: In an observational, cross-sectional, single-site study of 521 nursing ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Four studies investigated the influence of familial, marital, or parental status, with variable results about subsequent influence on quality of life and burnout. One study found that an increased number of tragic family life events (e.g., death of a relative or friend) was associated with increased depersonalization while controlling for other work-related changes and individual confounders ( Tortorelli et al, 2022 ). In another study, Akram et al (2017) found a significant correlation between spousal employment and total perceived quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies investigated the influence of familial, marital, or parental status, with variable results about subsequent influence on quality of life and burnout. One study found that an increased number of tragic family life events (e.g., death of a relative or friend) was associated with increased depersonalization while controlling for other work-related changes and individual confounders ( Tortorelli et al, 2022 ). In another study, Akram et al (2017) found a significant correlation between spousal employment and total perceived quality of life.…”
Section: Resultsmentioning
confidence: 99%
“… Blanco-Donoso et al (2021) found a significant interaction effect of daily depersonalization between daily work-family conflict and daily intention to leave one's job (β = 0.251, p < .01); as well as significant interaction effects with daily depersonalization and work-family conflict predicting daily vitality (β = -.526, p <.01). One study found no significant association between number of children and quality of life ( Tortorelli et al, 2022 ). In comparison, Ferriera and de Lucca (2015) found significant positive associations between depersonalization and having children or health problems.…”
Section: Resultsmentioning
confidence: 99%
“…The nurse works under strong and prolonged emotional tension [ 12 , 13 ]. In extreme situations, the lack of coping with stress, the characteristics and difficult of work in a given ward and the lack of team support lead to the formation of a burnout syndrome, which not only significantly reduces the quality of work, but also prevents nurses from further professional development [ 14 ]. Thus, in our manuscript, we conducted a review of studies on the prevalence and characteristics of burnout among nurses working in a neurology, geriatric, intensive care units and with patients infected with the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 99%